Pola Umum Bimbingan dan Konseling Perkembangan Berbasis Kelas bagi Mahasiswa PGSD - Resti Resti; Titi Sunarti; Zahra Fadla Amalia; Mutiara Citra Amalia; Faidah Faidah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Classroom-based developmental guidance and counseling has emerged as a strategic approach in elementary education, as students’ developmental support needs to be integrally embedded within daily instructional practices. Classroom teachers play a central role as facilitators of students’ academic, social, and emotional development; however, preservice elementary school teachers (PGSD students) often encounter limitations in their conceptual understanding and contextual application of guidance and counseling practices. This study aims to formulate a conceptual, integrative, and contextually relevant model of classroom-based developmental guidance and counseling to strengthen the professional competencies of PGSD students. The study employs a systematic comparative literature review with a qualitative-descriptive approach. Data were collected through a comprehensive review of scholarly literature retrieved from Google Scholar, ERIC, and SINTA databases, selected based on inclusion criteria encompassing the last ten years of publication, substantive relevance, and source credibility. Data analysis was conducted using thematic and comparative techniques to synthesize key concepts, principles, and models of developmental guidance and counseling. The findings indicate that a structured and preventive classroom-based developmental guidance and counseling model significantly enhances pedagogical competence, basic counseling skills, work readiness, and the development of professional and reflective dispositions among PGSD students in supporting the holistic development of learners.